Greatest Common Factor (GCF) of two numbers is the greatest factor that is common to both of them
To find the greatest common divisor of the given numbers or for algebraic expressions we have to follow the steps.
Step 1 :
List the prime factors of each of the given number. For algebraic expression we have to find factors of them.
Step 2 :
List the common factors of the given numbers or common factors.
Step 3 :
Multiply those common factors.
Find the greatest common divisor of following algebraic terms.
Example 1 :
7 x2 y z4, 21 x2 y5 z3
Solution :
7 x2 y z4, 21 x2 y5 z3
7 x2 y z4 = 7 ⋅ x2 ⋅ y ⋅ z ⋅ z3
21 x2 y5 z3 = 3 ⋅ 7 ⋅ x2 ⋅ y ⋅ z ⋅ z3
Common factors are 7, x2, y and z3
Multiplying common factors, we get
= 7x2yz3
So, greatest common divisor of the given algebraic terms is 7x2yz3.
Example 2 :
x2 y, x3 y , x2 y2
Solution :
x2 y, x3 y , x2 y2
x2 y = x2 ⋅ y
x3 y = x2 ⋅ x ⋅ y
x2 y2 = x2 ⋅ y ⋅ y
Common factors in the above terms are x2 and y.
By multiplying common factors, we get x2y.
So, greatest common divisor of the given algebraic terms is x2y.
Example 3 :
25 b c4 d3 , 35 b2 c5 , 45 c3 d
Solution :
25 b c4 d3, 35 b2 c5, 45 c3 d
25 b c4 d3 = 5 ⋅ 5 ⋅ b ⋅ c3 ⋅ d3
35 b2 c5 = 7 ⋅ 5 ⋅ b ⋅ b ⋅ c3 ⋅ c2
45 c3 d = 32 ⋅ 5 ⋅ c3 ⋅ d
Common factors in the above terms are 5 and c3.
By multiplying common factors, we get 5c3.
So, greatest common divisor of the given algebraic terms is 5c3.
Example 4 :
35 x5 y3 z4 , 49 x2 y z3 , 14 xy2 z2
Solution :
35 x5 y3 z4 , 49 x2 y z3 , 14 xy2 z2
35 x5 y3 z4 = 7 ⋅ 5 ⋅ x ⋅ x ⋅ x ⋅ x ⋅ x ⋅ y ⋅ y ⋅ y ⋅ z2 ⋅ z2
49 x2 y z3 = 7 ⋅ 7 ⋅ x ⋅ x ⋅ y ⋅ z2 ⋅ z
14 xy2 z2 = 7 ⋅ 2 ⋅ x ⋅ y ⋅ y ⋅ z2
Common factors in the above terms are 7, x, y and z2.
By multiplying common factors, we get 7xyz2.
So, greatest common divisor of the given algebraic terms is 7xyz2.
Factorise the following expressions and find the highest common factors for each set.
Example 5 :
4x2 y, 4x3 - 2xy
Solution :
4x2 y = 2 ⋅ 2 ⋅ x ⋅ x ⋅ y
4x3 - 2xy = 2x (2x2 - y)
Comparing these two set of factors, we see 2x in common. So, the highest common factor is 2x.
Example 6 :
6p + 3pq, 6p2
Solution :
6p + 3pq, from this we can factor out 3p.
6p + 3pq = 3p(2 + q)
6p2= 2 ⋅3 ⋅ p ⋅ p
By comparing the above set of factors, we see 3 and p are in common. So, the highest common factor is 3p.
Example 7 :
8pq, 4p2 q + 16pq2
Solution :
8pq = 2 ⋅ 4 ⋅ p ⋅ q
4p2 q + 16pq2 = 4pq (p + 4q)
By comparing these two set of factors, we get 4pq in common in both. So, the highest common factor is 4pq.
Example 8 :
x2 - 4xy + 4y2, x2 - 4y2
Solution :
x2 - 4xy + 4y2
Using the expansion of the formula for (a - b)2, we get
(a - b)2 = a2 - 2ab + b2
= x2 - 2 x (2y) + 4y2
= (x - 2y)2 -----(1)
x2 - 4y2 = x2 - (2y)2
Using the algebraic identity, (a - b)2 = (a + b) (a - b)
x2 - (2y)2 = (x + 2y)(x - 2y) -----(2)
Comparing (1) and (2), we get
(x - 2y)
So, the highest common factor is x - 2y.
Example 9 :
4x2 - 1, 4x2 - 4x + 1
Solution :
4x2 - 1 = (2x)2 - 12
Using the algebraic identity, (a - b)2 = (a + b) (a - b)
= (2x + 1)(2x - 1) ------(1)
4x2 - 4x + 1 = (2x)2 - 2(2x)(1) + 12
= (2x - 1)2 ------(2)
Comparing (1) and (2), we get the common factor.
(2x - 1)
So, the greatest common factor is 2x - 1.
Example 10 :
x2 - 1, x2 - 3x + 2
Solution :
x2 - 1 = x2 - 12
= (x +1)(x - 1) ------(1)
x2 - 3x + 2 = (x - 1)(x + 2) ------(2)
Greatest common factor = (x - 1)
Example 11 :
d - bd, 1 - 2b + b2, 1 - b2
Solution :
d - bd
Factor d, we get
= d(1 - b) -------(1)
1 - 2b + b2
Writing in the form of a2- 2ab + b2
= 1 - 2(1) b + b2
= (1 - b)2 -------(2)
1 - b2 = (1 + b) (1 - b) -------(3)
So, the greatest common factor is 1 - b.
Example 12 :
a3 - a2, 2a2 - 2a, a2 - 1
Solution :
a3 - a2
Factor a2, we get
= a2(a - 1) ------(1)
2a2 - 2a
Factoring 2a, we get
= 2a(a - 1) ------(2)
a2 - 1 = (a + 1)(a - 1) ------(3)
Comparing (1), (2) and (3), we get the common facor.
= (a - 1)
So, the greatest common factor is a - 1.
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Jan 20, 25 09:31 PM
Jan 20, 25 09:27 PM
Jan 15, 25 07:19 PM